Assistance BUMDes Gerbang Lentera, Lerep Village, Ungaran Barat in Increasing the Potential of Tourism Village (Indonesian Journal of Devotion and Empowerment, 2022)
Lerep village has a BUMDes with the name ‘Gerbang Lentera’. The selection of the BUMDes ‘Gerbang Lentera’ as the target of this service activity is because it is often appointed as a district delegate at the Central Java BUMDes festival and the Central Java Tourism Village festival. The Lantern Gate BUMDes business unit consists of BUMDesa Mart, which sells all the community's daily needs, Brilink, Tourism Villages, and other productive activities. One of the initiatives initiated by the BUMDes ‘Gerbang Lentera’ is the Lerep Tourism Village. The solutions offered in this service program are (1) Assistance to BUMDes ‘Gerbang Lentera’ managers as an effort to increase knowledge and ability to identify tourism potentials in Lerep tourist village, (2) Assistance to BUMDes ‘Gerbang Lentera’ managers in compiling a road map or a road map in developing the tourist village of Lerep. The method of implementing this activity is a Workshop / Focus Group Discussion (FGD) with the target of managing the BUMDes ‘Gerbang Lentera’. The four mentoring materials are (1) Legality Aspects, (2) Village Potential Identification Aspects, and (3) Business Plans & Feasibility Study Aspects. The result of this service activity is that BUMDes managers gain knowledge and improve their ability to identify tourism potentials in Lerep village and the availability of road maps in developing tourist villages. Desa Lerep memiliki BUMDes dengan nama ‘Gerbang Lentera’. Pemilihan BUMDes ‘Gerbang Lentera’ sebagai target kegiatan pengabdian ini adalah karena sering ditunjuk menjadi delegasi kabupaten pada festival BUMDes Jawa Tengah dan festival Desa Wisata Jawa Tengah. Unit usaha BUMDes ‘Gerbang Lentera’ terdiri dari BUMDes Mart yang menjual segala produk kebutuhan sehari-hari masyarakat, Brilink, Desa Wisata, dan kegiatan produktif lainnya. Salah satu yang digagas oleh BUMDes ‘Gerbang Lentera’ adalah Desa Wisata Lerep. Solusi yang ditawarkan dalam program pengabdian ini yaitu, (1) Pendampingan kepada pengelola BUMDes ‘Gerbang Lentera’ sebagai upaya dalam Peningkatan pengetahuan dan kemampuan untuk mengidentifikasi potensi-potensi wisata di desa wisata Lerep, (2) Pendampingan kepada pengelola BUMDes ‘Gerbang Lentera’ dalam menyusun road-map atau peta jalan dalam mengembangkan desa wisata Lerep. Metode pelaksanaan kegiatan ini adalah Workshop / Focus Group Discussion (FGD) dengan sasaran pengelola BUMDes ‘Gerbang Lentera’. Empat materi pendampingan yaitu: (1) Aspek Legalitas, (2), Aspek Identifikasi Potensi Desa, dan (3) Aspek Rencana Usaha & Studi Kelayakan. Hasil dari kegiatan pengabdian ini adalah pengelola BUMDes mendapatkan pengetahuan dan meningkatkan kemampuan dalam mengidentifikasi potensi-potensi wisata di desa Lerep dan tersedianya road-map/peta jalan dalam mengembangkan desa wisata.